SEJARAH DAN PELAKSANAAN KENDURI SKO DI DESA MUKAI MUDIK, KABUPATEN KERINCI. - Alhuzaini, Muhammad (UIN Imam Bonjol Padang, 2023)
This paper raises the main issue, namely regarding the history of the origins of the Sko kenduri tradition, and its implementation. The background of this research is the author's observation of a tradition that develops in the Mukai Mudik community where this tradition is carried out every five years, but in 2018 this tradition was not carried out, and also few know the origins of this Sko kenduri tradition. The purpose of this study is to describe the origins of the Sko kenduri tradition, and its implementation. To get answers to this, the method that the author uses in this study is historical research methods such as heuristics, source criticism, interpretation and writing, which are then described in writing. The results of this study indicate that the origins of Kenduri Sko in Mukai Mudik village date back to the entry of the Minangkabau people into this region in the 14th century, they asked for Sko to the king of Jambi with the aim of forming customs, and its implementation through several processes and many stages starting from preparation, implementation to feasting.